Monoclonal Antibody Preparation and Epitope Identification for Brucella melitensis Elongation Factor Tu - Zhao, Ningning; Jiang, Yue; Ming, Shuzhen; Liu, Sidang; Zhao, Xiaomin; Wang, Fangkun (Frontiers in Microbiology, 2019)
Elongation factor thermo-unstable (EF-Tu), an abundant multifunctional protein, is pivotal during protein synthesis and is an important antigen. Few studies have addressed the role of this protein in Brucella species, and the epitopes of this protein have not been reported. Here, we describe a monoclonal antibody (McAb), BD6, for EF-Tu in Brucella melitensis. Using western blotting involving a series of partially overlapping recombinant EF-Tu truncation peptides, a novel linear B-cell epitope, 110QTREHIL116 (EF), was identified. Alanine-scanning mutagenesis revealed that residues Q110, T111, R112, I115, and L116 were core residues involved in recognition. Sequence alignment suggested that the epitope peptide was conserved among bacterial species but differed by one amino acid residue (I115) from the host sequence. The epitope peptide was recognized by sera from B. melitensis-infected mice, and while recombinant epitope peptide induced a strong humoral immune response, the corresponding mouse peptide, QTREHLL, did not. These results suggested that I115 may be the key residue for the host immune system to distinguish between bacterial and self epitope EF sequences. Indirect immunofluorescence and western blotting assays showed that epitope peptide could be used in Saccharomyces cerevisiae, human embryonic kidney cell (HEK-293), and chicken fibroblast cell (DF1) expression systems and immunoprecipitation assay. Together, our results suggested that the McAb BD6 is a useful tool for further investigation of the potential functions of the EF-Tu protein in pathogen-host interactions, and that the epitope tag may be useful for application as a novel affinity tag to identificate of other becterial pathogens, especially convenient for the identification of intracellular bacteria.